Systematic evaluation of soil-based zeolite materials for the remediation of metal(loid)-contaminated water bodies - Zheting Chu; Huan Tang; Jiaxin Liang; Jing Li; Dazhong Yang; Ranhao Wang; Hong Chen (Soil & Environmental Health)
The synthesis of a diverse framework structure of zeolite materials using abundant natural soils as raw materials showcases the implementation of green chemistry principles and their feasibility for environmental engineering. However, no systematic evaluation of the soil-based zeolite materials for the remediation of metal(loid)-contaminated water bodies has been conducted. Herein, using the widely spread Chinese red soil and loess as raw materials, we have successfully synthesized eight zeolite materials and established a novel soil-based zeolite library. All eight zeolite types had different adsorption capacity for 10 metal(loid) ions, including As(III), As(V), Cd, Cr(III), Cr(VI), Cu, Hg, Ni, Pb, and Zn. The selectivity regarding different metal(loid) ions of zeolites was influenced by their framework structures, pH, speciation, and concentration of coexisting ions. A mechanism study revealed that ion exchange, electrostatic attraction, and chemical precipitation synergistically contribute to the interactions between soil-based zeolite materials and metal(loid)s. This work demonstrated the construction of a soil-based zeolite library from natural soils in line with green chemistry principles. Systematic metal(loid) adsorption data for diverse water bodies were presented, including deionized, tap, sea and river water. The information is important for future engineering application of soil-based zeolites in metal(loid)-contaminated water or soil remediation.